2013
DOI: 10.1124/mol.113.088302
|View full text |Cite
|
Sign up to set email alerts
|

Epoxyeicosatrienoic Acids Prevent Cisplatin-Induced Renal Apoptosis through a p38 Mitogen-Activated Protein Kinase–Regulated Mitochondrial Pathway

Abstract: Soluble epoxide hydrolase (sEH) catalyzes the conversion of epoxyeicosatrienoic acids into less active eicosanoids, and inhibitors of sEH have anti-inflammatory and antiapoptotic properties. Based on previous observations that sEH inhibition attenuates cisplatin-induced nephrotoxicity by modulating nuclear factor-kB signaling, we hypothesized that this strategy would also attenuate cisplatin-induced renal apoptosis. Inhibition of sEH with AR9273 [1-adamantan-1-yl-3-(1-methylsulfonyl-piperidin-4-ylurea)] reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 52 publications
(65 reference statements)
1
35
0
Order By: Relevance
“…Furthermore, knockout of Bax in mice leads to a significantly preservation of renal function under cisplatin treatment [9]. AR9273, an inhibitor of soluble epoxide hydrolase that inhibit the conversion of epoxyeicosatrienoic acids into less active eicosanoids, can also block mitochondrial Bax induction during cisplatin nephrotoxicity and interestingly, these anti-apoptotic effects may involve p38 mitogen-activated protein kinase (MAPK) signaling [56]. A recent study has further demonstrated that cisplatin-induced mitochondria dysfunction can be attenuated through increasing cGMP-dependent protein kinase I (PKG-I) activity.…”
Section: Mitochondrial Protective Agents For Cisplatin Nephrotoxicitymentioning
confidence: 99%
“…Furthermore, knockout of Bax in mice leads to a significantly preservation of renal function under cisplatin treatment [9]. AR9273, an inhibitor of soluble epoxide hydrolase that inhibit the conversion of epoxyeicosatrienoic acids into less active eicosanoids, can also block mitochondrial Bax induction during cisplatin nephrotoxicity and interestingly, these anti-apoptotic effects may involve p38 mitogen-activated protein kinase (MAPK) signaling [56]. A recent study has further demonstrated that cisplatin-induced mitochondria dysfunction can be attenuated through increasing cGMP-dependent protein kinase I (PKG-I) activity.…”
Section: Mitochondrial Protective Agents For Cisplatin Nephrotoxicitymentioning
confidence: 99%
“…NSAIDinduced intestinal ulcers are characterized by apoptosis of intestinal epithelial cells (Harada et al, 2015). EETs, sEH inhibition, and sEH gene deletion decrease apoptosis of cells (Luo et al, 2010;Liu et al, 2013). Therefore, an antiapoptotic role of TPPU in intestinal epithelial cells may be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogenic actions of EETs are dependent on activation of Src kinase and initiation of a tyrosine kinase phosphorylation cascade (27). EETs also prevent cisplatin-induced apoptosis in LLC-PK1 cells by preventing mitochondrial trafficking of Bax and cytochrome C and caspase 3 activation (82). Taken together, EETs have actions at the proximal tubule that promote sodium excretion, prevent cell death, and enhance cellular regeneration.…”
Section: Proximal Tubular Transportmentioning
confidence: 99%
“…EET analogs attenuate cisplatin-induced nephrotoxicity through a reduction in Bcl-2 protein family mediated proapoptotic signaling, reduced renal caspase 12 expression, and reduced caspase 3 activity (72). Likewise, EETs in LLC-PK1 epithelial cells attenuates mitochondrial trafficking of Bax and cytochrome c resulting in decreased caspase 3 activity and oxidative stress (82). Interestingly, the renal endothelial and epithelial antiapoptotic actions of EETs appear to work in concert with anti-inflammatory actions (72, 73, 82).…”
Section: Renal Inflammation and Apoptosismentioning
confidence: 99%